PEMANFAATAN LIMBAH BIJI SALAK DAN TONGKOL JAGUNG SEBAGAI CAMPURAN BETON YANG MENGHASILKAN KUAT TEKAN DAN KUAT TARIK MUTU TINGGI RAMAH LINGKUNGAN - Sabrian Rizki Fernanda (Civil Infrastructure Engineering and Architectural Design, 2020)
Along with technological development in the industrial revolution era 4.0, especially in construction sector needs to be innovated to improve the quality of infrastructure facilities. Innovations will be made on concrete as one of the components that most used in construction. The effort that will be done is to add additional material in the concrete mixture. The waste of corn cobs and Zalacca seeds need to be handled because it will cause environmental pollution. By changing corncobs and zalacca seeds into a concrete mixture. Corncobs contain 41% cellulose, 36% hemicellulose and 16% lignin (Huda, 2007). The cellulose content in corn cobs can provide compressive strength of 23 MPa and tensile strength of 2,42 MPa. This is influenced by lignin and hemicellulose in the womb. While zalacca seeds material are lightweight and strong so that zalacca seeds can be used as a reduction of cement. Innovations were made with the aim of utilizing corncobs as cement filler with a content of 10% and the utilization of zallaca seeds was waste for the utilization of cement with a content of 2,5% and 4%. So it can produce concrete with high compressive strength and tensile strength that is environmentally friendly.